1996
DOI: 10.1116/1.580387
|View full text |Cite
|
Sign up to set email alerts
|

Phase development in sputter deposited titanium dioxide

Abstract: We report the formation of highly oriented rutile titanium dioxide films. Films of a primarily amorphous nature were grown on fused silica by rf reactive sputter deposition using a Ti target and rare gas (Ne or Ar)-O2 discharges. Post-deposition annealing was done at 350–1150 °C in air for 60 minute intervals, followed by an air cool. The phase mixture of the as-deposited films, determined by x-ray diffraction, was of two types: (I) amorphous + rutile + anatase, or (II) amorphous + rutile. All phases were high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 0 publications
1
31
0
1
Order By: Relevance
“…11,[113][114][115][116] In general, TiO 2 films can grow in an amorphous and in two tetragonal crystalline structures; the rutile and the anatase phases, respectively. 117 The anatase phase exhibits interesting photocatalytic properties, 117 whereas the rutile phase exhibits one of the highest refractive indices in nature. 117 Deposition and/or annealing at high temperatures (700-900°C) have been reported to lead to the 110 formation of the rutile phase.…”
Section: B Phase Composition Tailoring By Hipimsmentioning
confidence: 99%
See 3 more Smart Citations
“…11,[113][114][115][116] In general, TiO 2 films can grow in an amorphous and in two tetragonal crystalline structures; the rutile and the anatase phases, respectively. 117 The anatase phase exhibits interesting photocatalytic properties, 117 whereas the rutile phase exhibits one of the highest refractive indices in nature. 117 Deposition and/or annealing at high temperatures (700-900°C) have been reported to lead to the 110 formation of the rutile phase.…”
Section: B Phase Composition Tailoring By Hipimsmentioning
confidence: 99%
“…117 The anatase phase exhibits interesting photocatalytic properties, 117 whereas the rutile phase exhibits one of the highest refractive indices in nature. 117 Deposition and/or annealing at high temperatures (700-900°C) have been reported to lead to the 110 formation of the rutile phase. 117 The anatase phase is generally obtained at lower temperatures, 117 whereas deposition at room temperature often leads to the formation of amorphous films.…”
Section: B Phase Composition Tailoring By Hipimsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Schematic illustration of the transformation of the film morphology larger than 14 nm (Zhang and Banfield, 1998;Hanaor and Sorrell, 2011). However, some investigations of the annealing effects on the transformation of TiO 2 films fabricated by sputter deposition (Wiggins et al, 1996), MOCVD (Won et al, 2001), and sol-gel dip-coating (Kim et al, 2002) reported that the transformation temperatures exceeded 600°C. Kumar et al (1993) investigated the difference in the transformation temperature between nanoparticle powder and nanoparticulate films both synthesized by the sol-gel method.…”
Section: Iii) Sintering Of Anatase Particles (700-900°c)mentioning
confidence: 99%